A COMPREHENSIVE STUDY ON THE RECENT PROGRESS ON THE QUALITY AND PRODUCTIVITY OF TASAR SILK WORMS AND THEIR FIBRES (International Journal of Food and Nutritional Sciences, 2024)
Commercially, there are four distinct types of natural silk available. Mulberry silk is the mostproduced type worldwide, contributing up to 90% of total production. Because of this, the silkproduced by the mulberry silkworm is usually referred to when the term "silk" is used in ageneral meaning